Degradation of aflatoxin in maize using Ferulic acid (phydroxy-3-methyl cinnamic acid) catalyzed by Hydrogen peroxide - Jacob, Nicholas M.; Wandiga, Shem O.; Kariuki, David K.; Madadi, Vincent O. (Journal of Food Sciences, 2020)
Purpose: The study aimed to determine the rate of degradation of aflatoxin in contaminated maize using ferulic acid catalyzed by hydrogen peroxide Methodology: 100 g of dried maize grain was grounded using a laboratory hammer mill and divided into 2 portions of 50 g each. 20 g sample was taken per portion and treated with 100 mL solution of methanol and deionized water in the ration of 8:1, 50 mL of Acetonitrile, 1 g NaCl and 4 g of anhydrous magnesium sulphate, then blended at 120 RPM for 30 min. Aflatoxin content in each extract was analysed using enzyme-linked immunoassay test kits and confirmed using high performance liquid chromatography (HPLC) coupled with fluorescence detector. Further experiments tested the effect of coating, size, concentration, catalyst and reaction time on degradation of aflatoxin in maize. Data analysis was conducted using SPSS and Microsoft excel. Findings: Four-hour treatment of contaminated maize with 0.5 mM ferulic acid reduced aflatoxin by 91.0% for whole maize, 90.5% for dehulled maize and 90.9% for ground maize. Addition of 20 mL of 0.5% hydrogen peroxide to the reaction mixtures increased degradation of aflatoxin load to 99.0% for whole maize, 99.1% for dehulled maize and 99.1% for ground maize within 4-hour reaction time. The rate of decontamination followed first order kinetics with R2 values of 0.919, 0.916 and 0.930 for the whole maize, dehulled maize, ground maize, respectively and achieved degradation half-lives of 43.59, 41.26 and 39.84 minutes in the same order. Unique contribution to theory, practice and policy: Ferulic acid combined with hydrogen peroxide is an effective degrader of aflatoxin in maize. The rate degradation is dependent on the nature of maize pre-treatment, the concentration of ferulic acid, and the catalyst. Ferulic acid and hydrogen peroxide reacted with the lactone ring of the coumarin moity of aflatoxin. Recommendations; Further studies on degradation of aflatoxin in maize should elucidate the pathways and metabolites formed in the ferulic acid degradation process and determine their toxicities